MODERN TECHNOLOGIES OF CAPITAL MANAGEMENT IN THE SYSTEM OF ECONOMIC SECURITY OF ENTERPRISES - YEPIFANOVA, Iryna; DZHEDZHULA, Viacheslav (Herald of Khmelnytskyi National University. Economic sciences, 2025)
Economic security management is a critical task for modern enterprises. The level of economic security determines an enterprise’s ability to resist internal and external disruptive factors. Despite a significant number of publications devoted to studying factors affecting economic security, the issues of determining the level of economic security of enterprises under conditions of uncertainty remain unresolved. One approach to determining the level of economic security under conditions of uncertainty is to use a mathematical model based on a second-order differential equation, which takes into account internal and external risk factors. The article analyzes modern technologies for managing the economic security of enterprises under conditions of uncertainty. In this context, the influence of risk and uncertainty factors on managing an enterprise’s economic security is considered. A second-order differential equation is proposed to determine the level of economic security under conditions of uncertainty. The first derivative of economic security over time is the rate of change in economic security, which depends on internal management decisions and adaptive strategies. The second derivative of economic security over time is the acceleration of security change, which characterizes the enterprise’s reaction to external influences. Solving the equation modelled the change in the enterprise’s economic security level under certain initial conditions. According to the modelling results, the primary influence on the level of economic security is the amplitude of random fluctuations and the damping and stabilization factors. The values of these factors can be determined analytically, expertly or experimentally.